Metyrapone-Associated Improvements in Health-Related Quality of Life in Cushing's Syndrome - Emese Mezôsi; Lynnette K Nieman; Carla Scaroni; Marco Boscaro; Timo Deutschbein; Natacha Driessens; Carmen E Georgescu; Marcin Motyka; Alicja Hubalewska-Dydejczyk; Barbara Jarzab; Dominique Maiter; Martin Reincke; et al. (European Journal of Endocrinology, 2026)
Abstract Objective This analysis describes the evolution of HRQoL over 36 weeks of metyrapone treatment in the PROMPT study, identifying patterns of early, delayed improvement, or persistence using item-level resolution. Design and Methods Longitudinal analysis of patient-reported outcomes from PROMPT (NCT02297945), a prospective, open-label, multi-country study of metyrapone in 49 evaluable adults with confirmed endogenous CS. HRQoL was assessed with the CushingQoL (0-100; higher = better QoL) and Tübingen CD-25 (0-100; higher = worse QoL) at Weeks 4, 12, 24, and 36. Item-level analyses characterised the pattern and timing of improvement. Within-patient changes were assessed using the Wilcoxon signed-rank test. Results Both questionnaires demonstrated significant overall improvement by week 36: CushingQoL increased by 10.4 points (p < 0.001; 44.7% with ≥10-point improvement), and Tübingen CD-25 decreased by −7.8 points (p = 0.01). Early responses (by week 12) involved eating behaviour and depression symptoms. Delayed improvements (consolidating at week 24–36) were observed in sexual activity, environment, and social domains. Bodily restrictions (−4.3 points, p = 0.203) and cognition (−6.8 points, p = 0.143) did not show improvement over the study period. Item-level analysis identified a cluster of symptoms, predominantly psychological health anxiety, physical appearance concerns, where burden remained elevated throughout the 36 weeks despite cortisol normalisation. Conclusions Metyrapone treatment is associated with meaningful, progressive HRQoL improvements across multiple symptom domains over 36 weeks, with a pattern consistent with rapid cortisol-mediated relief (eating, mood), delayed recovery in social and sexual domains, and persistent residual burden in symptom clusters likely driven by incomplete phenotypic reversal within the study timeframe.